The potential of Jakarta-Surabaya high-speed rail in developing tourism: Learning from Japan - Bangun, Cendera Rizky Anugrah; Pratiwi, Dian Fitriana; Dewi, Helga Liliani Cakra (Jurnal Studi Komunikasi, 2022)
The Shinkansen is the fastest bullet train in Japan. Shinkansen greatly improve the tourism economy in some cities in Japan. Shinkansen is extremely handy for foreign visitors and reduces the cost of visiting numerous places in Japan. As is known, MRT in Jakarta is one of the collaborative projects between Japan and Indonesia. Indonesia also has a 'semi-fast' train that travels between Jakarta and Surabaya at 140-145 km/hour. Learning from the Shinkansen in Japan, the Indonesian Semi-High-Speed Train also has the potential to increase the tourism sites in Indonesia with the help of a 'push and pull strategy.' This case study used interviews and literature reviews for data collection. In this study, after data was collected, it was used to analyse the mode of transportation for tourism destinations and the marketing strategy that can be used for this research. The result of this study is that Indonesia can also imitate the implementation of tour packages from Japan's railway and tourism system. Shinkansen connects tourist destinations in various cities (intercity), and it is hoped that the semi-fast train built by the Indonesian government can do the same thing. Railways as tourism transport are only one thing in developing tourist destinations. The other thing is, of course, related to integrated tourism planning